Surgical Management of Multiple Unilateral Maxillary Buccal Exostoses: A Case Report and Review of the Literature - Rumaisa Shahid; Aqsa Choudhry; Moazzam Hussain Siddiqui (Scientific Dental Journal, 2023)
These are benign overgrowths and have almost no potential for malignancy. They mostly develop around adolescence and slowly grow in size over the years. A 26-year-old patient presented with multiple unilateral bony protuberances on the outer and buccal aspects of the left maxilla. Poor aesthetics was the primary concern of the patient. Although the etiology of buccal exostoses remains unclear, a thorough history, clinical examination, and radiographic features lead to its diagnosis. The bony exostoses were removed through bone shaving. This study presented an uncommon and unique case of multiple unilateral maxillary buccal exostoses, along with their surgical management.